2022
DOI: 10.1002/smll.202204495
|View full text |Cite
|
Sign up to set email alerts
|

Ligand‐Engineered Quantum Dots Decorated Heterojunction Photoelectrodes for Self‐Biased Solar Water Splitting

Abstract: Statistical Analysis: PL lifetime values were fitted by tri-exponential decay fitting models with Origin, giving R-Square > 0.95, and standard error < 0.02 for the obtained results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…8 In addition, inorganic semiconductors possess a higher carrier mobility and can be applied to high-frequency electronic circuits, 56 while quantum dots and heterojunctions have higher sensitivity to light and are suitable for optical synaptic systems. 57,58 Additionally, some biocompatible synaptic devices especially the organic transistors can be degraded without any pollution and toxicity, which further facilitates the convergence of biotechnology and electronics in recording potential information from neurons. 59,60 Until now, major biological synaptic functions such as excitatory/inhibitory postsynaptic current (EPSC/IPSC), short/ long term plasticity (STP/LTP) and paired pulse facilitation (PPF) have been widely simulated by controlling presynaptic stimulation.…”
Section: Yuanwei Zhumentioning
confidence: 99%
“…8 In addition, inorganic semiconductors possess a higher carrier mobility and can be applied to high-frequency electronic circuits, 56 while quantum dots and heterojunctions have higher sensitivity to light and are suitable for optical synaptic systems. 57,58 Additionally, some biocompatible synaptic devices especially the organic transistors can be degraded without any pollution and toxicity, which further facilitates the convergence of biotechnology and electronics in recording potential information from neurons. 59,60 Until now, major biological synaptic functions such as excitatory/inhibitory postsynaptic current (EPSC/IPSC), short/ long term plasticity (STP/LTP) and paired pulse facilitation (PPF) have been widely simulated by controlling presynaptic stimulation.…”
Section: Yuanwei Zhumentioning
confidence: 99%
“…Cai et al reported shortchain-length monodentate 1-dodecanethiol ligands for Zndoped CuInS 2 (ZCIS) QDs by suppressing charge recombination. [55] Park and Park compared oleic acid (OA)treated CdSe and 1,2-ethanedithiol (EDT)-treated CdSe by the ligand-exchange method. OA is a longer ligand than EDT.…”
Section: Qds-based Photoelectrodementioning
confidence: 99%
“…(2018) [24] RuOx-TiO [25] Perovskite/Field's metal-Pt 8.5 0.8 −12 (0 V RHE ); NR; 7 (75%) BiVO 4 -Perovskite 0.35% 18 h(71%) NR Andrei et al (2018) [28] Pt-TiO 2 /CdS/Sb 2 Se 3 1.0 0.5 −20 (0 V RHE ); 3.4%; NR BiVO 4 -Sb 2 Se 3 1.5%; 10 h (90%) NR Yang et al (2020) [26] FTO/WO [17] Pt-C 60 pat-TiO 2 ball/GeSe [30] Pt-TiO 2 /CdS/Cu 3 BiS 3 6.5 0.9 −7 (0 V RHE ); 1.7%; 10 h (90%) BiVO 4 -Cu 3 BiS 3 2.04%; 20 h (90%) NR Huang et al (202)1 [31] FeCoO x /BiVO 4 [21] Mo-BiVO 4 [52] Si/p-GaN/InGaN 8.0 NR NR NR NR 1.9%; NR Guan et al (2018) [53] COP-TF@CNi 2 P 1…”
Section: The Pec Performance Of Td-czts-bivo 4 Tandem Cell In Natural...mentioning
confidence: 99%
“…[ 6 , 7 , 8 , 9 , 10 , 11 ] Some photosensitivity semiconductor materials, such as Si, BiVO 4 , TiO 2 , GaN, Cu(In,Ga)Se 2 , CdTe, GaAs, Sb 2 Se 3 , and so on, have been applied to PEC water splitting and showed remarkable hydrogen evolution performance. [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] Nevertheless, limited by the complex process and expensive raw materials of refining silicon, the rarity of indium in Cu(In,Ga)Se 2 , and the toxicity of cadmium in CdTe, researchers are looking for new low‐cost and environmentally friendly semiconductor materials to substitute for materials such as Si, Cu(In,Ga)Se 2 , and CdTe. [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] Fortunately, the low‐cost, environmentally friendly, and earth‐abundant kesterite Cu 2 ZnSnS 4 (CZTS) with an appropriate band gap (1.45 eV) and excellent light harvesting properties meets our needs for PEC solar water splitting.…”
Section: Introductionmentioning
confidence: 99%